Application of Hybrid Moran's I Index and SE Model on the spatial Impact and time dradient changes of regional development. Issue 1 (June 2021) - Yu, Linhui; Chang, Jing
Abstract: Spatial econometrics includes space, which has long been neglected in econometrics, into the model. To explore the two themes of spatial dependence and spatial heterogeneity is a branch of econometrics dealing with the spatial relationship of geographical units. Moran's I index test is a method to test the correlation of development in a spatial region, and the combination of spatial econometric model and Moran's I index test can add spatial effect to Moran's I index test and make a series of regression to get the regional correlation. According to the spatial econometric model, this paper collects the changes of per capita GDP scale level and real per capita GDP growth rate from 1980 to 2015, and applies Moran's model to the central, Western and eastern parts of China The results show that the spatial correlation of the development and growth of the eastern region is increasing year by year, the central region shows a fluctuating trend, and the spatial correlation of the western region shows a downward trend The change trend of I value predicts that the imbalance of regional development in China is gradually changing to the national development balance, which is consistent with the actual situation in China. It proves that the model combined with Moran's I index test is accurate and the prediction results are reliable.